2015
DOI: 10.1534/genetics.115.179499
|View full text |Cite
|
Sign up to set email alerts
|

The Pace of Hybrid Incompatibility Evolution in House Mice

Abstract: Hybrids between species are often sterile or inviable. This form of reproductive isolation is thought to evolve via the accumulation of mutations that interact to reduce fitness when combined in hybrids. Mathematical formulations of this "DobzhanskyMuller model" predict an accelerating buildup of hybrid incompatibilities with divergence time (the "snowball effect"). Although the Dobzhansky-Muller model is widely accepted, the snowball effect has only been tested in two species groups. We evaluated evidence for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 88 publications
1
50
2
Order By: Relevance
“…Indeed, given a rather short divergence time between Neanderthals and AMH, it is a priori unlikely that strong hybrid incompatibilities had evolved at a large number of loci before the populations interbred. It often takes millions of years for hybrid incompatibilities to evolve in mammals [42, 43], although there are exceptions to this [44], and theoretical results suggest that such incompatibilities are expected to accumulate only slowly at first [45, 46]. While this is a subjective question, our results suggest that genomic data—although clearly showing a signal of selection against introgression—do not strongly support the view that Neanderthals and humans should be viewed as incipient species.…”
Section: Discussionmentioning
confidence: 62%
“…Indeed, given a rather short divergence time between Neanderthals and AMH, it is a priori unlikely that strong hybrid incompatibilities had evolved at a large number of loci before the populations interbred. It often takes millions of years for hybrid incompatibilities to evolve in mammals [42, 43], although there are exceptions to this [44], and theoretical results suggest that such incompatibilities are expected to accumulate only slowly at first [45, 46]. While this is a subjective question, our results suggest that genomic data—although clearly showing a signal of selection against introgression—do not strongly support the view that Neanderthals and humans should be viewed as incipient species.…”
Section: Discussionmentioning
confidence: 62%
“…; Moyle and Nakazato ; Wang et al. ). Therefore, our measure of genetic parallelism might be interpreted as being inversely proportional to the strength of intrinsic barriers.…”
Section: Discussionmentioning
confidence: 99%
“…Using males from CC extinct lines, we performed the largest mapping study for reproductive traits in the CC, and identified several genetic associations with sperm morphology, sperm motility, and reproductive organ weights. Infertility was associated with a large region on chromosome X known to contain loci previously associated with hybrid incompatibility, sterility, and speciation (Payseur et al 2004;Storchova et al 2004;Good et al 2008Good et al , 2010Mihola et al 2009;Wang et al 2015;Balcova et al 2016). QTL allelic effects for most reproductive traits were driven by PWK/PhJ or CAST/EiJ haplotypes ( Table 3).…”
Section: Discussionmentioning
confidence: 99%